Neuropsychiatric Symptoms in Patients with Idiopathic Normal Pressure Hydrocephalus - Yumiko Kito; Hiroaki Kazui; Yoshihiko Kubo; Tetsuhiko Yoshida; Masahiko Takaya; Tamiki Wada; Keiko Nomura; Mamoru Hashimoto; Shingo Ohkawa; Hiroji Miyake; Masatsune Ishikawa; Masatoshi Takeda (Behavioural Neurology)
Objective: To clarify the characteristics of neuropsychiatric symptoms in patients with idiopathic normal pressure hydrocephalus (iNPH).